BAUXITE RESOURCE EXPLOITATION IN GREECE VS SUSTAINABILITY - Anagnostou, Ch. (Bulletin of the Geological Society of Greece, 2010)
In the central part of Greece bauxite ore deposits are systematically exploited since more than fifty years, initially by a French industrial group and since few years by a Greek investment group. This “economical” activity uses the non renewable mineral resources of bauxite, non renewable energy sources, as well as significant amount of water and it exports to the environment pollutants and byproducts. CO2, NOx, F, PAHs are diffused to the atmosphere, polluting the soil of the adjacent area. Big amount of red mud is deviated to the sea, covering an extended shelf area and parts of deeper marine areas. The aim of this work is to evaluate this “economic” activity using principles of the sustainability science. In its broadest definition, sustainability refers to the ability of a society to continue functioning into the future without being forced into decline through the exhaustion or overloading of key resources.